Effect of Exercise Intensity in Glut4 Expression on Type 2 Diabetes Mellitus Rat - Rahmi, Rahmi; Machrina, Yetty; Yamamoto, Zulham (Universitas Negeri Semarang, 2021)
Glucose transporter4 (GLUT4) is the main glucose transporter in skeletal muscle. Impaired GLUT4 expression plays a role in the disorders of glycemic homeostasis such as Type- 2 Diabetes Mellitus (T2DM). Exercise can increase the GLUT4 expression in skeletal muscles so that glucose can get into the cells faster. The intensity of exercise is an important factor in reducing blood glucose levels in patients with T2DM. This study used stored biological material of gastrocnemius muscle from 15 T2DM models of Wistar rats. Rats were divided into three treatment groups namely P0 (no exercise, control), P1 (moderate-intensity continuous exercise), and P2 (vigorous-intensity continuous exercise), and treated for 8 weeks. Glut4 expression was determined by real time-PCR. The relative expression of the Glut4 gene was calculated using the Livak formula. Moderate-intensity exercise increased Glut4 expression by 2.39 times while vigorous-intensity exercise increased Glut4 expression 2.56 times compared to control. The vigorous-intensity continuous exercise expressed higher Glut4 expression than the moderate- intensity continuous one.